The Influence Of Career Development And Self-Regulation On The Organizational Commitment Of Civil Servants In The Transportation Agency Of Kubu Raya Regency - Fernanda, Muhammad Dini Rizki; Mahdi, Irfan (UNIVERSITAS PAKUAN, 2024)
This study aims to identify the influence of Career Development and Self-Regulation on the Organizational Commitment of civil servants in the Transportation Agency of Kubu Raya Regency. The research employs an associative approach, with a saturated sampling technique. The respondents consist of 45 employees working in the Transportation Agency of Kubu Raya Regency. Data analysis was conducted using multiple linear regression analysis with SPSS 25 software. The tests conducted in this study include validity testing, reliability testing, normality testing, linearity testing, and multicollinearity testing. Hypothesis testing was performed using simultaneous testing (F-test) and partial testing (T-test). Based on the results of hypothesis testing, both simultaneous (F-test) and partial (T-test), it is found that Career Development and Self-Regulation simultaneously have a positive and significant effect on Organizational Commitment. Partially, Career Development has a positive and significant effect on Organizational Commitment, while Self-Regulation has a positive but not significant effect on Organizational Commitment.